Flexible Methodologies as Tools for Implementing Dynamic Changes in the Management System - Inna LEVYTSKA; Alona KLYMCHUK; Olena KOVALENKO; Nataliia BRYTANSKA; Oleksandr MAZUR (Communications of International Proceedings, 2020)
Dynamic changes in the control system are due to changes in the external and / or internal environment. The risks of negative results after the introduction of changes are significantly reduced by using systemic training methodologies. Such methodologies are flexible management methodologies based on the Agile Manifesto. The authors propose the adaptation of known approaches to the introduction of flexible management methodologies together with the principles of change management. This uses a synergistic combination of the principles of the Agile Manifesto and the rules for implementing Cotter's changes. Among them: creating a sense of urgency; support groups, the vision of change, informing, removing obstacles, creating short-term victories, consolidating improvements, fixing changes. The authors consider a practical example of using the proposed method of implementing changes in the universities of Ukraine in the restructuring of the educational process in a pandemic. This adaptation takes into account the peculiarities of educational management. The introduction of changes concerned the translation of the educational process into a full distance format. Educational management has its own characteristics. The quarantine experience of VNTU and NUBIP universities testifies to positive changes based on already existing distance and blended learning portals. But the full remote format revealed problems of the unwillingness of a group of teachers and students to work completely remotely, insufficient server power, vulnerabilities of the testing module. To solve such problems, special training of teachers was organized, for students in rural areas - the use of various information channels, changes in the testing system. In addition, it was important to introduce changes for active teacher-student communication; teacher-teacher (at the suggestion of users); to introduce the electronic dean's office module at all faculties, to start using the procedures of forming the electronic archive and to implement the procedures of free choice of disciplines by students. It was also necessary to use security tools. Comparative tables of the introduction results of dynamic project groups of improvement of management systems of training and procedures of processes realization of training online testify to the efficiency of using flexible methodologies taking into account theories and practices of the introduction of changes. This approach allows you to create a dynamic management system of the organization, which quickly perceives and implements change.
Keywords: Management System; Change Management; Sound Management Methodologies; Agile; Educational Management; Quarantine Period (Pandemic).